The Impact of Television Advertisements on Student Decision-Making Process for College Admission: An exploratory study in India - Gautam S Bapat; Prema Mahale; Arya Kumar; Raghavan Srinivasan (ACHSM, 2021)
COVID-19 drove universities throughout the world forcing Higher Education Institutions (HEIs) to go online or virtual. Admissions advertising and student recruitment were two of the sectors that were severely hit. Internet-based advertising has to entirely replace the old advertising environment. Although certain institutions were still able to conduct virtual tours, forums, and information sessions, the amount of involvement differed among colleges and universities. An exploratory study was conducted to investigate how effective Internet advertisements were in influencing students' admission decisions. During the academic year, 2020-21 at several institutions in India's western region, data were collected using the snowball sampling approach on 930 freshly enrolled students. The findings show that the efficacy of Internet ads for university admission is negatively correlated with the student's age group. Surprisingly, the study discovered that both rural and urban students were equally interested in online ads, and that family background had no impact on receptiveness to internet advertisements. (*The paper was presented at the 2nd Conference on Business Data Analytics: Innovation in emerging trends in management data analytics. Apeejay School of Management, Dwarka, Delhi, India. November 2021)